2018
DOI: 10.3390/ijerph15010068
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Practice and Associated Factors among Residents in Wuhan, China

Abstract: Background: This study aims to examine the prevalence and predictors associated with self-medication, and related consequences in Wuhan, China. Methods: Two-hundred-sixty residents were interviewed from randomly selected four districts of Wuhan, China. A modified version of Anderson’s health behavioral model was used in the survey to collect information of self-medication behavior. Multivariable logistic regression analyses were used to measure correlates of the prevalence of self-medication. Results: Nearly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
5
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 26 publications
13
100
5
13
Order By: Relevance
“…This study was conducted among 200 participants in urban and 200 in rural area. This study revealed that in urban and rural area most of the participants are males [15][16][17] In the present study most of the participants in urban area belonged to nuclear family (51.0%) and rest are belonged to joint (26.5%) and three generation family (22.5%) while in rural area half of the participants belonged to joint family and those belonging to nuclear family were (40.0%) and three generation family (10%) respectively. On the other hand study conducted by Dutta et al in Chennai, Tamil Nadu reported that 62.5% participants were belong to nuclear family and rest are belong to third generation and joint family.…”
Section: Discussionsupporting
confidence: 47%
“…This study was conducted among 200 participants in urban and 200 in rural area. This study revealed that in urban and rural area most of the participants are males [15][16][17] In the present study most of the participants in urban area belonged to nuclear family (51.0%) and rest are belonged to joint (26.5%) and three generation family (22.5%) while in rural area half of the participants belonged to joint family and those belonging to nuclear family were (40.0%) and three generation family (10%) respectively. On the other hand study conducted by Dutta et al in Chennai, Tamil Nadu reported that 62.5% participants were belong to nuclear family and rest are belong to third generation and joint family.…”
Section: Discussionsupporting
confidence: 47%
“…Residents in Wuhan, China practiced self medication for cough and cold the most (55.1%). 29 Due to the ease of procuring the medications from the hospital or the working place several drugs belonging to different groups was self medicated among the healthcare workers in this study. NSAIDS was the most common drug self medicated in all the participants, followed by antihistamine and drugs acting on GIT.…”
Section: Nursing Staff Paramedicalmentioning
confidence: 99%
“…Based on the results of the present study, the drugs used by the women for self-medication were mostly for the treatment of colds and included, respectively, analgesics, antibiotics, anti-allergy drugs, and hypnotics; the results were more or less similar to those of other studies. For instance, in a previous study, cold and coughing were the most common causes of self-medication (38), and in another study, self-medication drugs used among adolescents consisted of non-steroidal antiinflammatory drugs (NSAIDs) or analgesics, cold stop and anti-cough drugs, anti-allergy drugs, and anti-acids (39). In another study conducted in Iran, herbal medicines had the highest rate, followed by analgesics and antibiotics, in the self-medication program of the people (37).…”
Section: Discussionmentioning
confidence: 95%